PENDIDIKAN ANAK MODEL ORANG TUA DI JEPANG - Iriyanto Widi Suseno (Diponegoro University, 2018)
Each nation has its own educational pattern, according to its cultural values. To see the character of a banga need to examine how the education of children based on the cultural values it embraces. Japan is known as a nation whose nation is disciplined, hardworking, and independent. This kind of Japanese character can be formed through the ways parents in Japan in educating their children in the family environment. This study would like to reveal the pattern or way parents in Japan in educating their children. The length of this study is important when looking at the fact that the Japanese state to date has become a developed country and has strong economic stability and security. The role of the characters that shape the mental attitude of the Japanese becomes an important factor. The position and function of the family in the education of Japanese character as the leading sector. Parents as role models for children at home, namely in the introduction and planting value of empathy, discipline, ethics and Gambaru.Keywords: children's education, family, parents, character